Relevance of Islamic Values and Local Wisdom in the Implementation of Maddoa’ Tradition in Pinrang Regency - Majid, Anugrah; Yahya, Yahya; Basir, Muhammad; Hidayat, Rian (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2025)
The Maddoa’ tradition not only serves as a social activity but also as a means to strengthen the identity and values of local wisdom in the Pinrang district community. Islamic values, as the guiding principles for the majority of the people in Pinrang, influence various aspects of daily life, including traditional activities. This research seeks to question how the integration of Islamic values with local wisdom manifests in the Maddoa’ tradition in Pinrang. This type of research is field research. The approaches used include a normative Sharia approach and a sociological approach. The results of this study indicate that the Maddoa’ tradition not only preserves cultural heritage but also strengthens the collective awareness of the importance of gratitude and devotion to Allah SWT, enriching the spiritual and social life of the local community. This makes the Maddoa’ tradition not only an adat event but also a means to reinforce social and spiritual bonds among the residents, demonstrating the synergy between local culture and Islamic teachings.